Actinidia arguta (Hardy Kiwi) Root Extract Exerts Anti-cancer Effects via Mcl-1-Mediated Apoptosis in Cholangiocarcinoma. (17th February 2019) - Zhao, Xiangxuan; Wen, Feng; Wang, Wei; Lu, Zaiming; Guo, Qiyong
Abstract: Cholangiocarcinoma (CCA) is a highly aggressive and chemoresistant liver malignancy. Thus, identification of strategies to overcome insensitivity to apoptosis and growth inhibition is a growing focus of research in this malignancy. This study evaluated the potential anti-cancer effects of an ethanol extract from the Actinidia arguta (Hardy Kiwi) root (RAE) on CCA. Our data demonstrated that RAE decreased cell viability and induced apoptosis by activation of Caspase 3, Caspase 8, and Poly (ADP-ribose) polymerase (PARP) in two CCA cell lines. RAE induced a decrease in Mcl-1 in cultured CCA cells and in xenograft CCA tumors. Administration of RAE every other day led to significant growth inhibition in tumor burden xenograft CCA mice. Western blotting analysis of paired human CCA and normal adjacent tissues from the same patient revealed that CCA tissues exhibited significantly higher Mcl-1 expression than normal tissues. Taken together, our findings demonstrated the anti-cancer effects of RAE on CCA both in vitro and in vivo . These data suggest that RAE may be a promising anti-CCA agent and could be beneficial in the treatment of CCA through the targeting of Mcl-1.